Evaluation of soft tissue norms on lateral cephalograms in babol - Vali ollah Arash; Manouchehr Rahmati Kamel; Abbasali Ostad Rahimi; Reza Ghorbanipour (Babol University of Medical Sciences, 2017)
Introduction: Soft tissue has a prominent role in diagnosis and treatment plan in orthodontics. Facial proportions are measurable on lateral cephalograms. The purpose of this study was to compare the means of the normal soft tissue proportions of babol people with the norms of Caucasians. Materials & Methods: In this cross-sectional study, 100 cases with normal occlusion and proportional facial profile were participated from babol. After taking radiographs and tracing, the soft tissue variables were analyzed to find means and standard deviations. The data were compared with Caucasian's norms using T-test. Results: The norms of following variables in babol people were significantly different from those of Caucasians: facial convexity, nasolabial angle, upper lip thickness, chin soft tissue thickness and protrusion of lower lip. Conclusion: In babol, people have a more convex profile, more prominent nose and lower lip than caucasians.